Polymer Micelle Directed Magnetic Cargo Assemblies Towards Spin‐wave Manipulation. Issue 15 (8th July 2021) - Manuguri, Sesha; van der Heijden, Nadine J.; Nam, Seong J.; Narasimhan, Badri Narayanan; Wei, Bohang; Cabero Z., Marco A.; Yu, Haiming; Granville, Simon; McGillivray, Duncan J.; Brothers, Penelope J.; Williams, David E.; Malmström, Jenny
Abstract: Spin‐wave based technologies that use collective oscillation of electrons termed magnons have been proposed for future computing landscapes due to their low energy consumption and high data transfer speeds. Magnonic crystals, materials with magnetic properties periodically varied in space, are central to such technologies. However, they are currently limited by the lithography techniques used for the magnetic patterning. To address this issue, bottom‐up self‐assembly using polymer templates to order magnetic cargo is presented. In this work, block copolymer micelles are used as templates to direct the organization of polyoxometalate (POM) molecules into organized assemblies. The structural organization of these assemblies is evaluated using microscopy and scattering techniques. The organized POM assemblies are demonstrated to modulate spin‐waves excited in permalloy thin films. This work demonstrates the first use of a bottom‐up approach to realize the fabrication of a magnonic assembly at the nanoscale. It further paves the way to achieve magnon‐mediated self‐assembled computing architectures. Abstract : The use of block copolymers as templates is demonstrated for organizing polyoxometalate assemblies. The organized assemblies are demonstrated to modulate spin‐waves excited in permalloy thin films. This work demonstrates the first use of a bottom‐up approach to realize the fabrication of a magnonics assembly at the nanoscale. This further paves the way to achieve magnon‐mediated self‐assembled computing architectures.